Čto otmečaet Gulja? O prazdnikah v proizvedenijah Ljudmily Ulickoj - Vojvodić, Jasmina (Array, 2007)
In this paper the author examines the meaning of (celebrating) holidays in the story ‘ Gulia’ and other works by Liudmila Ulitskaia. The semantics of Russian prazdn- are discussed, along with the general social-cultural function of holidays. As these can be regarded as “ empty time” (cf. É. Durkheim and M. Epshtein), the way it is “ filled in” becomes highly relevant for the heroine of Ulitskaia's story and her characterization.